PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 7 KOTA PEKANBARU - Dedi Arianto; Zariul Antosa; Munjiatun Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The background of the problem of this research was low of the result IPA at the fifth grade SD Negeri 7 Pekanbaru. It was because of the researcher using communicative method that made students less pay attention to the lesson well and also learning not created with fun and interest situation. Less giving award for success of students had been made motivation learning of students was low. Quantum Teaching model could be increase the result IPA at the fifth grade SD Negeri 7 Pekanbaru. The researcher was chosen students of fifth grade SD Negeri 7 Pekanbaru as an experimental class school year 2014/2015. The total of students as many as twenty six peoples consist of fourteen men and twelve women. The research was action class research (PTK), the research was conducted in two cycles and each cycle consist of two times meeting with final test every single cycle. The goal of this research was increased the result IPA at the fifth grade SD Negeri 7 Pekanbaru at main material and character. The result of this research showed that applying Quantum Teaching model could be increase the result IPA at the fifth grade SD Negeri 7 Pekanbaru. At the first data the average score of the result study was 65,38. After had been done the action at the first cycle got increased became 69,08 from the first data. Then, at the second cycles increased became 85,54. Based on explanation above it could be said applying Quantum Teaching model could be increase the result IPA at the fifth grade SD Negeri 7 Pekanbaru.Keyword : Quantum Teaching, Learning Achivement IPA